Phase II study of neo-adjuvant chemotherapy for locally advanced gastric cancer. Issue 1 (1st August 2016) - Chang, Alex Yuang-Chi; Foo, Kian Fong; Koo, Wen-Hsin; Ong, Simon; So, Jimmy; Tan, Daniel; Lim, Khong Hee
Abstract : Background: Neoadjuvant chemotherapy improves survival of locally advanced gastric cancer patients. However, benefit is limited and the best regimen remains controversial. Objectives: Our primary objective of this prospective, multicenter phase 2 study was to evaluate the pathological complete response rate (PCR) with 2 cycles of docetaxel and capecitabine. Methods: To be eligible, patients had to have histologically documented gastric cancer, a ECOG performance status 0 or 1, T3or4 Nany M0 staging after oesophagogastroduodenoscopy (OGD), endoscopic ultrasound (EUS), CT scan of thorax and abdomen, and negative laparoscopic examination and peritoneal washing. Eligible patients received two cycles of intravenous docetaxel 60 mg/m 2 on day 1 and oral capecitabine 900 mg/m 2 two times per day from day 1 to day 14 every 3 weeks. We evaluated the response by CT scan and EUS. The patients underwent curative resection with D2 lymphadenectomy subsequently. Results: 18 patients were enrolled in the study: 66% were male and the median age was 60 years. 17 patients had T3 disease at diagnosis. There was no pCR noted. 4 patients had a partial response of 22% (95% CI: 7–42%), 8 patients had stable disease and 3 patients had disease progression. The median survival was 17.1 months with 3 long-term survivors after at least 3 years of follow-up. The treatment was well tolerated with neutropenia being the most common toxicity. We observed 22% grade III and 33% grade IV neutropenia, but no neutropenic fever or death was observed from chemotherapy. Conclusion: Neo-adjuvant chemotherapy with docetaxel and capecitabine has limited activity against GC. More effective treatment regimens are needed urgently. Trial registration number: NCT00414271.